2015
DOI: 10.7235/hort.2015.14042
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Combined Treatment of Hot Water with Green Tea Extract and NaCl on the Postharvest Quality of Fresh-cut Burdocks

Abstract: This study investigated quality changes in fresh-cut burdocks treated with hot water and anti-browning agents. The combined treatment using both heat treatment and anti-browning agents delayed the browning of burdocks, especially for those dipped in hot water and a solution of green tea extract plus NaCl. This treatment reduced the respiration rate and inhibited the growth of microorganisms more than heat treatment alone. The organoleptic quality of burdocks treated with the combined method proved to be the be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 54 publications
1
1
0
Order By: Relevance
“…From day 2, the control group displayed a progressive browning, whereas the tea polyphenol-treated group maintained a superior appearance quality. These results align with previous studies on fresh-cut burdock [25], dragon fruit [20], and lotus root [21] where TPs, as natural antioxidants, effectively curbed enzymatic browning in fresh-cut produce by neutralizing excessive ROS produced during processing, thereby decelerating oxidation rates. The result of Figure 1b indicated that the appearance quality corresponded to the browning index results.…”
Section: Browning Index and Appearancesupporting
confidence: 91%
“…From day 2, the control group displayed a progressive browning, whereas the tea polyphenol-treated group maintained a superior appearance quality. These results align with previous studies on fresh-cut burdock [25], dragon fruit [20], and lotus root [21] where TPs, as natural antioxidants, effectively curbed enzymatic browning in fresh-cut produce by neutralizing excessive ROS produced during processing, thereby decelerating oxidation rates. The result of Figure 1b indicated that the appearance quality corresponded to the browning index results.…”
Section: Browning Index and Appearancesupporting
confidence: 91%
“…These natural antioxidants, which prevent the oxidation of organic molecules, are very critical for food preservation. Chang and Kim [ 103 ] noted that the ethanolic extract of green tea exhibited PPO inhibition activity (80%). The authors reported that the PPO inhibition activity correlated with the flavonoid compounds, such as catechin.…”
Section: Extracts Derived From Plants or Herbs Sourcesmentioning
confidence: 99%